The Meaning And Practice Of Gold Jewelry Investment In Building Financial Resilience: A Phenomenological Study Of Madurese Muslim Families - Sahliyah; Elfira Maya Adiba; Farid Ardyansyah (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2026)
This study aims to understand the meaning and practices of gold jewelry investment in building financial resilience among Madurese Muslim families. This research employs a qualitative approach using a phenomenological method, focusing on the subjective experiences of participants in interpreting the ownership and use of gold jewelry as an investment instrument. Data were collected through in-depth interviews, observation, and documentation involving several Madurese Muslim families who actively utilize gold jewelry. The findings reveal that gold jewelry is not only perceived as a symbol of social status and cultural identity but also as a flexible and easily liquidated form of emergency savings. The investment practices are carried out gradually, adjusted to the economic capacity of each family, and influenced by religious values and local traditions. Furthermore, gold jewelry plays a significant role in maintaining family economic stability, particularly in times of crisis or urgent financial needs. Therefore, gold jewelry investment serves as an adaptive strategy that integrates economic, social, and cultural aspects in strengthening family financial resilience.